Resveratrol aumenta a motilidade espermática, previne a lipoperoxidação e melhora as defesas antioxidantes em testículos de ratos hipertireóideos - Ourique, Giovana de Moraes (2012)
Hyperthyroidism may lead to an increase in oxidative stress (OS) in testis, may cause male reproductive disorders, among them, the loss in the sperm quality. The effect of resveratrol (RSV) on sperm motility and on OS parameters in testis of euthyroid and hyperthyroid rats was investigated. Hyperthyroidism was induced by daily intraperitoneal injection (i.p.) of triiodothyronine (T3) (100 μg/kg, i.p.) for six weeks. After two weeks, concomitantly to T3 treatment, animals received daily injections of RSV at dose of 1 mg/kg e 10 mg/kg (i.p.) during four weeks, totaling six experimental weeks. At the end of experimental period animals were euthanized for removal of organs. Sperm of cauda epididymal was collected for sperm motility and morphology analysis Testis were homogenized for determination of lipoperoxidation by lipid hydroperoxides and thiobarbituric reactive substances (TBARS) levels; activity of antioxidant enzymes superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and glutathione-S-transferase (GST); and non-enzimatic antioxidant glutathione (GSH). Hyperthyroid rats presented lower sperm motility, higher lipid hydroperoxides and TBARS levels, lower CAT and GPx activities and higher GST activity in testis than animals of control groups. RSV treatment at doses of 1 mg/kg and 10 mg/kg was able to prevent the loss on sperm motility induced by hyperthyroidism. In addition, RSV decreased lipid hydroperoxides and TBARS levels; reversed the decrease in CAT and GPx activities; and also prevented the increase in GST activity caused by hyperthyroidism in adult rat testis. Together these data show the protective effect of RSV in the testis, preserving sperm motility, and protecting testis against oxidative damage caused by hyperthyroidism, which suggests the RSV as a possible target of studies in the search for therapeutic strategies in order to preserve testicular function.